Wind Power in View : Energy Landscapes in a Crowded World. - Pasqualetti, Martin (Sustainable world., 2002)
More than ever, travelers are encountering a different sort of landscape, one not only of nature but of technology. Wind Power in View is the first authoritative discourse on the aesthetic impact of wind turbines on the landscape and what can be done about it. It is a detailed and thoroughly illustrated discussion of the issue from several different perspectives. The book also provides an overview of the status of wind energy at the dawn of the new millennium, examines some of the ongoing battles, and offers guidelines on minimizing its visual impact. Taking examples from the United States, Ge.